STRATEGI PENGELOLAAN SUMBERDAYA PESISIR BERBASIS MASYARAKAT DI KABUPATEN INDRAGIRI HILIR (Studi Kasus Kawasan Panglima Raja Kecamatan Concong) - Zulkarnain '; Amrizal ' (Berkala Perikanan Terubuk, 2010)
The research was conducted on July to August 2008, it was aimed to knowthe characteristics of fishermen in Panglima Raja Indragiri Hilir Regency and toidentification and description about strategy on coastal resources management inPanglima Raja Indragiri Hilir Regency. The reserach was using by groundedresearch as the same case study method.The result of this research was concluded, the social economy condition offishermen in Panglima Raja among of them depend on fishing activities, loweducation in elementry school only. The culture among of them is DuanoCommunity, their activities depend on the sea, the house is called “Kajang” andthen there are malay culture in coastal zone these is knowing in religion andnationalism celebrate.The srategy on coastal resources managament based community inPanglima Raja was compiled that are : Strategy of institution development,Strategy of accompanying, research and training, Strategy of infrastructuredevelopment and environmental management, Strategy of generating incomedevelopment and Strategy of marketing acces development of fisheries product.